COMPARATIVE STUDY OF FORWARD WINGTIP FENCE AND REARWARD WINGTIP FENCE ON WING AIRFOIL EPPLER E562 - Hariyadi, Setyo; Sutardi, Sutardi; Widodo, Wawan Aries; Pitoyo, Bambang Juni (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2020)
The perfect wing is a dream that many airplanes has manufactured have been striving to achieve since the beginning of the airplane design. There are some aspect that most influence in aircraft design lift, drag, thrust, and weight. The combination of these aspects leads to a decrease in fuel consumption, which reduces pollution in our atmosphere and increase in economic revenue. One way to improve aircraft performance is to modify the tip of the wing geometry, which has become a common sight on today?s airplanes. With computational programs, the effects on drag due to wingtip devices can be previewed. This research was done numerically by using turbulence model k-? SST. Reynolds number in this research was 2,34 x 10 4 with angle of attacks are 0o, 2o, 4o, 6o, 8o, 10o, 12o, 15o, 17o and 19o. The model specimen is wing airfoil Eppler 562 with winglets. Two types of wingtips are used: forward and rearward wingtip fence. From this study, it was found that wingtip fence reduced the strength of vorticity magnitude on the x axis compared to plain wings. The leakage of fluid flow effect at the leading edge corner of the wingtip, giving pressure gradient and slightly shifting towards the trailing edge. this occurs in the plain wing and rearward wingtip fence but does not occur in the forward wingtip fence..